Community-Based Empowerment in The Perspective of MaqÄá¹£id Al-SharÄ«Ê¿a - Tasya Hadi Syahputri; Muhammad Anwar Fathoni (State Institute of Islamic Studies (IAIN) Salatiga, 2023)
The purpose of this research is to explore the role of community-based empowerment in the Depok UKMP community. Community-based empowerment as one of the bottom-up economic development is needed to enhance the economic performance of the city of Depok. TheÂ economy of Depok has not shown consistent indicators of improvement over the last decade. Accordingly, bottom-up economic developmentÂ is needed in which the community can participate in it. This research is case study research with a descriptive qualitative approach. The dataÂ used are primary data and secondary data. The role of empowerment is analyzed usingÂ indicators from al-kulliyyÃ¡t al-khamsah maqÃ¡sid alsharÃ'aÂ to review worldly and ukhrowi aspects. The results of the study indicate that the UKMP community hasplayed a role in empowering its members. Empowerment is perceived inÂ imensions of spiritual, material,Â educational, and human rights protection. MSMEs can empower themselves through the role of the community to increase their capacities, developÂ knowledge, create independence, and support economic improvement.